The discourse and the event in the teaching of philosophy: notes on the notion of self-writing - Vandresen, Daniel Salesio; Gelamo, Rodrigo Pelloso [UNESP] (Univ Federal Santa Maria, 2024)
The purpose of this text is to reflect on the teaching of philosophy in high school, questioning a certain use of representational discourse as a way of producing subjection relations and seeking to think of discourse as liberation through the attitude of cohabiting problems. This diagnosis is supported by a bibliographic review, covering the Foucauldian concepts of self-care and self-writing, as well as Pierre Hadot's ideas on ancient philosophy. The descriptive course of this work starts initially from the problematization of philosophical discourse as a diagnosis of two ways of doing philosophy: one, which is the representational discourse and the other, which is of a philosophy as a cohabitation of problems. Then, we developed the notion of writing the self as a way of stressing the relationship with oneself, with others and with the world, which contributes to thinking about philosophy as an exercise of the self, that is, as an attitude of restlessness, which makes from philosophical training, a problematization of everyday practices as a form of attention to the present and a less abstract relationship in teaching. Finally, we conclude that thinking about philosophical writing as a problematization of the self constitutes a way of freeing the individual from the subjection produced by the processes of a reproductive writing and, then, opening up to the encounter with the unusual, with the strange, with what makes us uneasy and causes us to change.
Keywords: Care of yourself; Self-writing; Philosophy teaching; Problems cohabitation